2018
DOI: 10.1016/j.bjps.2017.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Trends in post-mastectomy breast reconstruction types at a breast cancer tertiary referral centre before and after introduction of acellular dermal matrices

Abstract: This study showed that since ADM introduction to our centre, more breast reconstructions have been of the implant-only type with consequent reductions in the more complex and expensive autologous techniques. Implant-only procedures that incorporated ADM use had similar complication rates to those that did not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…1 However, compared with implant-based reconstruction, autologous tissue transfer is associated with longer operative times, longer hospital length of stay, and higher intraoperative blood loss which can require blood transfusion in the perioperative period. 2,3 Transfusion in patients undergoing autologous free tissue transfer for breast reconstruction occurs at rates up to 8%. 4 Perioperative resuscitation strategies have been in the spotlight in many different surgical specialties with conflicting conclusions.…”
mentioning
confidence: 99%
“…1 However, compared with implant-based reconstruction, autologous tissue transfer is associated with longer operative times, longer hospital length of stay, and higher intraoperative blood loss which can require blood transfusion in the perioperative period. 2,3 Transfusion in patients undergoing autologous free tissue transfer for breast reconstruction occurs at rates up to 8%. 4 Perioperative resuscitation strategies have been in the spotlight in many different surgical specialties with conflicting conclusions.…”
mentioning
confidence: 99%
“…These rates are in accordance with previous series involving experienced surgeons, which reported 2.6% epidermolysis rates and 1.3% full skin flap necrosis, 8,9 results mirrored by another study with a workload of 30 reconstructions/surgeon/year. 10 A randomized controlled trial including 92 reconstructions had very low rates of infection (2%) and skin necrosis (1%). 11 The present study benefits from its single-surgeon We conclude that future studies should include a minimum workload/surgeon/year or provide this information.…”
Section: Association Between Variables Was Evaluated By Chi-squared Tmentioning
confidence: 99%
“…The complication rates lie below the 5% threshold, except for seroma formation (14%). These rates are in accordance with previous series involving experienced surgeons, which reported 2.6% epidermolysis rates and 1.3% full skin flap necrosis, results mirrored by another study with a workload of 30 reconstructions/surgeon/year . A randomized controlled trial including 92 reconstructions had very low rates of infection (2%) and skin necrosis (1%) .…”
Section: Patient Tumor and Treatment Characteristicsmentioning
confidence: 99%
“…It was not a surprise that Kankam HKN, et al in January 2018 [4] reported that in 264 patients over the last 18 months the ADM-assisted IBBR percentage has increased from 16% to 52% of all breast reconstruction procedures, stepping down the DIEP from 49% to 34%. Which can be a sign of a pending shift in the breast reconstruction in the following years.…”
Section: Clinical Scenariomentioning
confidence: 99%